ON CONTINUITY OF A (3,1,ρ)-METRIC - Čalamani, Sonja; Dimovski, Dončo (Matematichki Bilten, 2014)
A given \((3,1,ρ)\)-metric \(d\) on a set \(M\), induces more than one topology \(τ\) on \(M\). In general the map \(d\) from the third power of \((M,τ)\) to the real numbers with the usual topology is not continuous. In this paper we consider one of the topologies \(τ\) on \(M\) and some additional conditions that will imply the continuity of \(d\).